Moldova s Phenomenon: Can Foreign Investments Help Out of the Poverty Circle? - PÎŞCHINA, Tatiana; Fortuna, Romeo (European Journal of Economics and Business Studies, 2017)
The aim of this paper is to further develop findings on the forces of globalization, which, in a positive and in a negative manner affect economic growth of various nations worldwide, both creating opportunities and posing challenges whilst deepening inequalities between developed and developing economies. The dilemma of global growth is pressing and especially relevant for the economies that currently lack economic quality, which makes them vulnerable to what this paper coins the 'vicious circle' of poverty. The findings in this study interpret changes in economic structure overtime based on the results of the analysis of quantitative and qualitative indicators of growth of national and international relevance. The case study of Moldova is expanded from author s previous contributions to demonstrate a few of the possible alternatives to create and sustain economic growth with quality, even in conditions of globalization obviously hazardous for this small economy. The paper shows how the emphasis on innovations and appropriate policies is supposed to make up for the lack of other key resources available to the developed industrial economies. It takes up an important instrument of foreign investments to demonstrate how and in what way those can be used for economic restructuring towards innovation-driven growth. It inquires how such approach will create competitive advantages helping the developing economies to break out of the ‘poverty circle towards qualitative economic growth. Among other considerations, the paper concludes on the importance of capturing the opportunities presented by the ongoing Fourth Industrial Wave, which, if approached correctly, may help many nations to ‘leapfrog through several stages of the structural ladder, enabling them to pursue qualitative economic growth. This article is interesting for businesses, including entrepreneurs and potential investors, as well as for the governmental organizations and public authorities. It provides both an evaluation of Moldova's position on the international socio-economic arena in context of globalization, and suggests action-points and recommendations potentially supporting the growth of the private sector, at the same time fighting poverty and enforcing sustainable economic growth.
Keywords: globalization, inequality, economic growth with the development, developing countries, ”vicious circle of poverty”, “structural ladder”, investment, infrastructure, high-technology, technology, innovation